Quantitative Criterion to Predict Cell Adhesion by Identifying Dominant Interaction between Microorganisms and Abiotic Surfaces - Yuan, Hao (Langmuir : the ACS journal of surfaces and colloids, 2019)
Cell adhesion is ubiquitous and plays an important role in various scientific and engineering problems. Herein, a quantitative criterion to predict cell adhesion was proposed by identifying the dominant interaction between microorganisms and abiotic surfaces. According to the criterion, the dominant interaction in cell adhesion could be identified as a Lewis acid-base (AB) interaction or electrostatic (EL) interaction via comparison of two expressions containing the electron-donor characteristics of the microorganism (γmv-) and abiotic surface (γsv-) and their ζ potentials (ζm, ζs). The results revealed that when dominated by the AB interaction, adhesion would decrease with increasing [Formula: see text]. However, when the EL interaction was dominant, adhesion would decrease with increasing (ζm + ζs)2. We have verified the criterion based on the adhesion of microalgae, bacteria, and fungi onto various surfaces obtained via our experiments and available in literature studies. The results demonstrated that the criterion had important implications in the prediction of cell adhesion in various applications